Brute force polarisation of xenon-129 - O'Neill, Jason Darren (2008)
In recent years the number of applications using NMR spectroscopy of hyperpolarised noble gases has expanded rapidly. The signal enhancement hyperpolarisation provides has led to its implementation in studies as diverse as materials science and biological imaging. 129Xe in particular, with its easily deformed electron cloud, is proving to be a uniquely sensitive probe for nanoporous structures. At present hyperpolarises gas production is limited to optical pumping (SEOP). In this study we investigate another approach, the brute force technique. At very low temperatures and high magnetic fields the Boltzmann distribution of spins for magnetic nuclei is heavily biased in a single direction. At temperatures below 10 mK and in magnetic fields of 15 T, 129Xe polarisations exceeding 40% are attainable. The utilisation of the brute force technique is hindered by the extraordinarily long relaxation time need for this polarisation to occur. In this study, we give details of our investigations of two relaxation catalysts, oxygen and helium-3. It is shown that paramagnetic molecular oxygen causes rapid relaxation of solid xenon at temperatures as low as 500 mK. We report on the enhanced relaxation, by liquid 3He of xenon films adsorbed on to silica gel and exfoliated graphite substrates. The investigation of this mechanism is extended to other magnetic nuclei and improved rates of relaxation are observed in 13C and 1 H. Details are also given, of how this mechanism of relaxation can be halted by the addition of superfluid 4He. Unique observations in the 129Xe NMR spectra are reported, providing a unique opportunity to study the coupling between individual layers of 129Xe atoms. Finally, a novel mechanism of cooling, by the filtering of energetic atoms through a porous ceramic membrane, is investigated.